2004
DOI: 10.1080/02640410410001729982
|View full text |Cite
|
Sign up to set email alerts
|

String vibration dampers do not reduce racket frame vibration transfer to the forearm

Abstract: In this study, we examined the effect of string vibration damping devices on reducing racket frame vibration transfer to the forearm. Twenty participants volunteered to hold a tennis racket stationary in a forehand and backhand stroking position while tennis balls were fired at 20 m x s(-1) towards two impact locations, the node of vibration and the dead spot. A three-way analysis of variance with repeated measures on damping condition, impact location and stroke condition was performed on the data. The resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The use of vibration dampeners on the strings as well as grip size have also been proposed to have an effect on the development of lateral epicondylitis 15. Studies revealed, however, that there were no significant differences in vibration amplitude22 or discomfort ratings23 between players with dampened and non-dampened strings. Similarly, there was no difference in forearm muscle firing patterns when oversizing or undersizing the recommended size of the racquet grip by 6.25 mm (1/4 inch) 24.…”
Section: Prevalence Of Specific Tennis Injuriesmentioning
confidence: 99%
“…The use of vibration dampeners on the strings as well as grip size have also been proposed to have an effect on the development of lateral epicondylitis 15. Studies revealed, however, that there were no significant differences in vibration amplitude22 or discomfort ratings23 between players with dampened and non-dampened strings. Similarly, there was no difference in forearm muscle firing patterns when oversizing or undersizing the recommended size of the racquet grip by 6.25 mm (1/4 inch) 24.…”
Section: Prevalence Of Specific Tennis Injuriesmentioning
confidence: 99%
“…9 Li found that vibration dampers do not reduce the vibrations felt by the hand and arm with regard to the approximately 120 Hz resonance of their racket. 10 This project did not measure the vibrations felt by the hand, so again, perhaps the mainly higher modes that were damped in this project do not contribute largely to the vibrations felt by the hand following an impact. This conclusion is supported by the lower maximum vibrational amplitude found in the higher frequency modes ͑see Fig.…”
Section: E Discussion Of the Effects Of Vibration Dampersmentioning
confidence: 97%
“…While some publications have discussed specifically the vibrational behavior of the tennis racket, 7,8 as far as the author is aware, no research has employed SPI to directly observe the vibrational behavior of a tennis racket and no research has yielded detailed information regarding the first 12 mode shapes. In addition, several authors studied the effects of vibration dampers on the mechanical performance of the tennis racket, [9][10][11][12] but again no research has directly studied the changes in vibrational behavior caused by vibration dampers. The vibration damping systems, of which there are several distinct designs, are advertised as lessening uncomfortable high frequency vibrations in the racket that lead to a bad "feeling" in the racket as experienced by the player.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study has shown no significant differences in amplitude of vibration at the resonant frequency for the wrist or the elbow when damped and non-damped impact were compared 17. They also noted no significant differences in discomfort ratings between damped and undamped impacts 18.…”
Section: Aetiology and Tennis Biomechanicsmentioning
confidence: 94%